Spark Plasma Sintering of Materials Advances in Processing and Applications - Cavaliere, Pasquale; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes spark plasma sintering (SPS) in depth. It addresses fundamentals and material-specific considerations, techniques, and applications across a broad spectrum of materials. The book highlights methods used to consolidate metallic or ceramic particles in very short times. It highlights the production of complex alloys and metal matrix composites with enhanced mechanical and wear properties. Emphasis is placed on the speed of the sintering processes, uniformity in product microstructure and properties, reduced grain growth, the compaction and sintering of materials in one processing step, various materials processing, and high energy efficiency. Current and potential applications in space science and aeronautics, automation, mechanical engineering, and biomedicine are addressed throughout the book.
Process Fundamentals -- Al-Based Materials -- Mg-Based Materials -- Cu-Based Materials -- Ti-Based Materials -- Metallic Glasses Materials -- Fe-based Materials -- Ni-based Materials -- W-based Materials -- High Entropy Alloys -- High Temperature Materials.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering